E-Governance System Challenges and Cloud Computing Benefits in E- Governance - Ali, Alaa Ibrahim Mahmood (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The global rise in the communications is affecting the life of societies particularly our modes of work, learning and interacting . Presently, nearly all organizations as well as the official government are presenting their facilities via internet. E-Governance is an approach to implement ideal system through ICT to help find a better citizen involvement. The various customers of the E- governance like government, citizens, as well as businessmen. A successful e- governance regime has to be cost effective, easy and dependable to be maintained. Unluckily, recent technologies are insufficient to cover the entire need of E-governance. The cloud computing is a modern approach to computing that targets improve the ways of communication and storing of data in a protected environment through the internet find a policy. cloud computing is an active application advancement that help find a resolution for all E-Governance infrastructure development with low price as well as short time. This research introduces e-governance challenges and benefits supplied by cloud computing that complement and sustain e-Governance.